Elastic scattering of 274.5 Mev deuterons and its optical model analysis - Testoni, J. E.; Rosenblatt, Jorge; Mayo, Santos (North Holland Publishing, 1965)
Fil: Testoni, J. E. Comisión Nacional de Energía Atómica; Argentina